PEMBIAYAAN SMK NEGERI DAN SWASTA DI DIY DALAM ERA OTONOMI - Wagiran Wagiran (Universitas Negeri Yogyakarta, 2004)
Abstract This research aims to describe vocational high school (VHS) educational budget pattern, its problems, and also the effort solve the problems. This research was conducted at stage as well as private VHSs in Yogyakarta. A sample of 11 state and 26 private VHSs was established. Data were collected by using questionnaire, interview, and document and then analyzed both quantitatively and qualitatively. The results indicate that: (a) Educational budget of state and private VHSs comes from government finance and parents support category, (b) Educational budget of state and private VHSs come more from government than from parents support, whereas that of private VHSs come more from parents than from government. (c) The biggest problem faced by state as well as private VHSs is the delay of payment from the government and the parents. Keywords: Educational Budget Pattern, Vocational High School (SMK)